Juridical Analysis of Flood Management in The Context of Drainage Management In Cirebon City - Pahdiansyah , Rangga Dwi; Zulfa , Atha Salsabila; Mufarrihunnufus , Moh; Gunawan, Moh Sigit; Yusup Permana, Deni (CV. Science Tech Group, 2025)
Flood management is a series of efforts to prevent, reduce, and deal with the impacts of floods, which can threaten human safety, damage the environment, and disrupt social and economic activities. This study aims to analyze the effectiveness of a regulation on flood management and drainage management in Cirebon City. This research will use Qualitative methods. Data collection was carried out through interviews. This study found that limited trained human resources and insufficient budget hinder the implementation of flood management and drainage improvement programs. The condition of drainage infrastructure that needs maintenance, such as the number of channels damaged or blocked due to sedimentation and closure by buildings, is also a factor that causes waterlogging and flooding. This research contributes to the development of legal science, especially in environmental law and spatial planning law.